Student reflections on enabling success and overcoming barriers - Chanock, Kate; Ivancevic, Kali; Price, Katie; Appo Van Commenee, Wesley (Journal of Academic Language and Learning, 2025)
In October 2024, students from five Australian universities participated in a panel session of AALL’s professional development series, “Connect. Inspire. Share.” (aall.org.au/connect-inspire-share-catalogue-2/). Here, three of them summarise their reflections on how they have succeeded despite barriers to study, and the role of individual consultations with Learning Advisers in their success.